The philosophical potential of the hesichastic antropological strategy - Сідоріна, Є. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article is dedicated to the anthropological prospects of filosophic understanding of the Hesichastic practice